Development of A New Colorimetric-Flow System Approach for The Determination of Cefotaxime Sodium in Pharmaceutical Formulations - Hamrawi , Nawras Majid Hassouni; Hammood, Mohammad K. (Iraqi Journal of Science, 2025)
A new colorimetric-flow injection method has been developed and validated for the detection of Cefotaxime sodium in pharmaceutical formulations. This method stands out for its rapid and sensitive nature. The formation of a brown-colored complex between Cefotaxime sodium and the Biuret reagent in a highly alkaline environment serves as the basis for the detection. The intensity of this colored complex is measured using a custom-built Continuous Flow Injection Analyzer, enabling accurate quantification of Cefotaxime sodium. Optimization studies of the chemical and physical parameters such as dilution of Biuret reagent, effect of the medium basicity, flow rate, sample loop and others have been investigated. The calibration graph was linear in the range of 10-650 μg.ml-1 for each blue & green light source, with correlation coefficient r = 0.9509 & 0.9991 for blue & green respectively. The limit of detection was 5 μg.ml-1 for diluting the lowest concentration in the calibration graph. The RSD% was less than 0.7% for 50 and 100 μg.ml-1 (n=6) concentration of Cefotaxime sodium in each light source. Cefotaxime sodium was successfully determined using the proposed approach in two pharmaceutical products. the conventional approach (UV-spectrophotometry at wavelength 388 nm) and the newly devised method analyses were compared using the conventional add approach and the t-test at a 95% confidence level revealed that there was no discernible difference between the two procedures.